Ð‘Ð¸Ð¾Ñ…Ð¸Ð¼Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ Ð¸ Ð¼Ð¾Ñ€Ñ„Ð¾Ð»Ð¾Ð³Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ Ð°ÑÐ¿ÐµÐºÑ‚Ñ‹ ÑÐµÐ·Ð¾Ð½Ð½Ð¾Ð¹ Ð¸ Ð¸ÑÐºÑƒÑÑÑ‚Ð²ÐµÐ½Ð½Ð¾Ð¹ Ð°ÐºÐºÐ»Ð¸Ð¼Ð°Ñ†Ð¸Ð¸ ÐºÐ°Ñ€Ð°ÑÑ ÑÐµÑ€ÐµÐ±Ñ€ÑÐ½Ð¾Ð³Ð¾ - Gulevsky, A. K.; Grischenkova, Ye. A.; Relina, L. I.; Zhegunova, Ye. G.; Chaplay, Ye. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
Seasonal biochemical and morphological changes in tissues of the goldfish Carassius auratus were studied. Preparation for winter was shown to require remodeling in tissues on morphological and biochemical levels of organization. This remodeling is of labile and reversible nature, as the parameters investigated in the deacclimated fish in winter are similar to the summer ones. At the same time a switch of fish organism to winter regimen requires more complicated and longer reorganization of systems, since an abrupt decline of water temperature in summer resulted in 100% mortality of the fish within 5 days.